Analysis of the effect of career planning, training and career development on employee job performance - Mohamad, Jupri; Abdul Malek, A Tambi; Mustafa, Mamat; Sukono, .; Ruly, Budiono; Abdul Talib, Bon (2019)
Career Planning, Training and Career Development is one of several factors that affect Employee Job Performance. This paper aims to examine and analyze Career Planning, Training and Career Development influencing Employee Job Performance at PT. Pos Indonesia (Persero) Tbk Regional V Bandung. Analyzes were performed using multiple linear regression models with the help of SPSS version 16 software to analyze data. The results of hypothesis testing and analysis show that Career Planning, Training and Career Development has a significant positive effect on the Employee Job Performance of PT. Pos Indonesia (Persero) Tbk Regional V Bandung.